PENGEMBANGAN MEDIA BERBASIS MACR PENGEMBANGAN MEDIA BERBASIS MACRO MEDIA FLASH 8 UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SEKOLAH DASAR: PENGEMBANGAN MEDIA BERBASIS MACRO MEDIA FLASH 8 UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SEKOLAH DASAR - Nirya, M. Haikal Alfarisi; Putera, Rafhi Febryan (Journal of Practice Learning and Educational Development, 2025)
This research is motivated by the use of IT available in schools has not been optimally used by teachers. Innovative and fun media for students has not been developed and technology-based learning media has not been developed. So teachers need to improve their ability to process technology-based learning media so that students do not get bored. The PBL model has never been used for the use of learning media, especially technology-based media. Based on these problems, this study aims to develop learning media in the form of Macromedia Flash 8 media using the Problem Based Learning (PBL) model in Pancasila Education learning in grade IV of elementary schools that is valid, practical and effective. This type of research is development research (R&D) using the ADDIE model. The ADDIE model consists of five steps, namely: analysis, design, development, implementation, and evaluation. The designed media is then validated by a validator using a validation sheet in the form of a questionnaire. Product validation consists of material experts, media experts and language experts. For product practicality, it is done by filling out a questionnaire of teacher responses and student responses. Then, for effectiveness, it is done by giving evaluation questions to students. The subject of the product trial was at SDN 17 Pasaman, West Pasaman Regency and the subject of product research was at SDN 07 Pasaman, West Pasaman Regency. This type of research is development research (R&D) using the ADDIE model. The ADDIE model consists of five steps, namely: analysis, design, development, implementation, and evaluation. The designed media is then validated by the validator using a validation sheet in the form of a questionnaire. Product validation consists of material experts, media experts, and language experts. For product practicality, it is done by filling out a teacher response questionnaire and student responses. Then, for effectiveness, it is done by giving evaluation questions to students. The subject of the product trial was at SDN 17 Pasaman, West Pasaman Regency and the subject of product research was at SDN 07 Pasaman, West Pasaman Regency. The results of the study showed that the Macromedia Flash 8 media obtained material validity of 95% (very valid), language validity of 70% (quite valid), and media validity of 97.23% (very valid). Based on the results of teacher responses and student responses in the trial school, it is known that learning using Macromedia Flash 8 media is very practical with the percentage of practicality from teacher responses in the trial school being 92.5%, and the percentage of practicality from student responses being 95.72%. The percentage of teacher responses in the research school was 95% and the percentage of student responses was 96.5%. The effectiveness test reached 92% with a very effective category. The conclusion of the study is that Macromedia Flash 8 media with the Problem Based Learning model is proven to be valid, practical, and effective in supporting the learning process of Pancasila Education in grade IV of elementary school.